Efektifitas Intervensi Manajemen Waktu dalam Menurunkan Prokrastinasi Akademik di Kalangan Remaja - Dicky Dienial Habibillah Wijaya; Djudiyah Djudiyah; Rizki Maulana Hidayatullah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study explores the effectiveness of a time management intervention in reducing academic procrastination among first- and second-semester undergraduate students at several universities in Malang. A quasi-experimental method was employed involving two groups with a total of 20 participants: 10 students in the experimental group who received a time management workshop and 10 students in the control group. The research instrument was the Academic Procrastination Scale developed by Onwuegbuzie. The intervention was conducted over six sessions focusing on techniques such as the Pomodoro Technique, Eisenhower Matrix, distraction management, relaxation, reward systems, to-do lists, leisure time management, and weekly scheduling. Data were collected through questionnaires and analyzed using an independent samples t-test and the nonparametric Mann–Whitney test. Participants were selected using a random sampling technique, and the academic procrastination scale was used as the primary measurement instrument. The results indicate that the time management intervention was effective in reducing academic procrastination, suggesting important implications for the development of more effective educational strategies. This research is expected to contribute to the design of more effective intervention programs to increase the academic productivity of students in higher education.